Understanding Basic Literacy and Information Literacy for Primary Students - Nur Fitria, Tira (Journal of Contemporary Issue in Elementary Education, 2023)
This research describes basic literacy and information literacy for elementary (primary) students. This research is library research. The analysis shows that primary students should understand six basic literacies, including 1). Literacy Read and Write (ability to understand the contents of written texts both explicit and implicit). 2). Numerical Literacy (ability to use basic mathematical symbols and numbers to solve practical problems and analyze mathematical information). 3). Scientific Literacy (ability to understand natural phenomena both scientific literacy and social phenomena). 4). Financial Literacy (ability to understand finance, concepts, management, risks, and skills in the financial sector. 5). Digital Literacy (ability to use digital media, create communication content, and filter information). 6). Cultural Literacy and Civic (ability to understand values, rights, and obligations as Indonesian citizens). Besides, understanding information literacy is also important for students. Several benefits of literacy are 1) training basic skills to read, write and count, 2) developing to think critically and logically when entering society and facing any situation. 3) having good literacy development correlates with better learning and communication skills, solving logical problems even academic achievement.